The new frontiers in computational modeling of material structures. (August 2016) - Regli, William; Rossignac, Jarek; Shapiro, Vadim; Srinivasan, Vijay
Abstract: We are witnessing the emergence of a new paradigm in the modeling of material structures . It stems from the digitization of manufacturing and is fueled by advances in additive manufacturing and material science. This paper strives to provide a critical examination of this new paradigm in a historical and technological context and to show that it requires non-trivial extensions and generalizations of the classical theoretical foundation and algorithmic solutions originally developed for solid modeling. Specifically, it requires new models and data-intensive representations for materials, physical behavior, and manufacturing processes across multiple scales. In particular, we argue that most computational tasks that support traditional and emerging manufacturing may be formulated systematically and addressed in terms of relations ( conversions, synthesis, change propagation updates, verification, and other harmonization activities) among four views (manifestations) of an engineered artifact: Functional, which captures the design constraints and tolerances on shape, properties, and behavior; Designed, which represents a toleranced design that satisfies these constraints; Planned, which defines a manufacturing process plan; Simulated, which models the expected outcome of the process plan; and a Real sample set of physical artifacts produced by executing the process plan on a particular manufacturing technology. Based on this formulation, we outline important directions for a research agenda aimed at enabling, driving, and amplifying further advances in digital design and manufacturing. Graphical abstract: